Penerapan Permainan Engklek dan Ceramah untuk Meningkatkan Pengetahuan tentang Pemberantasan Sarang Nyamuk Siswa Sekolah Dasar Negeri Krekah, Bantul - Metina Ayu Yunitasari; Lucky Herawati; Indah Werdiningsih (Poltekkes Kemenkes Yogyakarta, 2018)
Dengue Hemorrhagic Fever (DHF) is a health problems that tends to increase, in terms of the case number and the spread. Elementary school students are the vulnerable groups for this disease. Therefore, health education to uplevel their knowledge about the eradication of Aedes’ breeding places should be conducted. One of the methods is through traditional games as the media. The purpose of this research was to know the effect of Engklek game and lecture on the knowledge level of preventing DHF among students of Krekah Elementary School of Bantul. Thestudy was a quasi experiment with non-equivalent control group design. The study subjects were 82 students of IV grade, who were assigned into 2 groups, i.e. 41 as the experiment group and 41 as the control group. The data were analyzed by using Mann-Whitney test at 0,05 level of significance. Results of the study show that Engklek game as health education media is significantly able to improve students’ knowledge (p-value = 0,001), i.e. about 18 %.